Knowledge Management Practices Among Students of Higher Education: A Knowledge Transfer Perspective - Rai, Rahan Singh (Dristikon: A Multidisciplinary Journal, 2026)
This study investigates knowledge management (KM) practices in higher education institutions, with a particular emphasis on effective knowledge transfer (EKT) from the learning perspective of student’s. By applying a descriptive and explanatory research design, five key attribute as distant relations, student receptive capacity, shared consensus, student inherent motivation, and communication encoding competence were analyzed. The structured questionnaire employed a five-point Likert type scale ranging from 1 means "strongly disagree" to 5 means "strongly agree" was distributed for final sampled 200 bachelor and master level students using a purposive sampling approach. Findings from multivariate analysis portrayed that student receptive capacity, inherent motivation, and communication encoding competence were significant predictors of effective knowledge transfer (EKT). Remarkably, student inherent motivation and receptive capacity demonstrated the strongest correlation with knowledge transfer. Conversely, distant relations and shared consensus were found to have no significant impact of EKT within this academic background. These findings recommend that institutes of higher learning should prioritize encouraging students’ intrinsic motivation and absorptive skill, along with faculty communication skills, to enhance the students learning capability in the knowledge-based economy.